Educação nutricional para pacientes renais crônicos em diálise - Casas, Juliane (2014)
Chronic renal failure patients are exposed to several nutritional issues, including restrictive diet. Adequate nutrition is of vital importance in the treatment of those patients and nutritional education is a very important matter since it can change the patient s behavior and therefore improve their nutritional status, decreasing risks of inadequate diets. Special attention must be directed to electrolytes, proteins, energy and liquid intake. Objectives: To assess the effects of a specific nutritional education program developed for dialytic patients and designed to give information for adequate decisions and contributions to patient s self-care; To assess changes in feeding habits and laboratorial tests that may be induced by the program. Methodology: 27 patients in HD, randomly chosen, who received a course that consisted of classes about: renal failure, HD and nutrition; liquids, dry weight and interdialytic weight gain; electrolytes and proteins. Before and after the course, patients underwent comparative food questionnaires and were evaluated about their nutritional knowledge. Blood levels of albumin, phosphorus, potassium and interdialytic weight gain, body mass index were also compared in the two moments. The course were evaluated through the gain of knowledge and by open questions about the course itself. Results: Patients demonstrated a very low level of comprehension of basic questions about nutrition before the course (24% of correct answers). This comprehension improved after the course (60% of correct answers), but food questionnaires, interdialytic weight gain and laboratorial data were similar in both moments, despite a very good satisfaction evaluation of the course by patients. Conclusions: The educational program induced a gain of knowledge in nutritional aspects for dialysis patients, but did not induce significant changes of the quality/amount of food intake nor in the laboratorial levels. Positive assessment of the program was observed. It s possible that changes in the nutritional aspects and in laboratorial level demand more time of observation